2015
DOI: 10.1088/1475-7516/2015/10/035
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting sensitivity on tilt of power spectrum of primordial gravitational waves after Planck satellite

Abstract: By taking into account the contamination of foreground radiations, we employ the Fisher matrix to forecast the future sensitivity on the tilt of power spectrum of primordial tensor perturbations for several ground-based (AdvACT, CLASS, Keck/BICEP3, Simons Array, SPT-3G), balloonborne (EBEX, Spider) and satellite (CMBPol, COrE, LiteBIRD) experiments of B-mode polarizations. For the fiducial model n t = 0, our results show that the satellite experiments give good sensitivity on the tensor tilt n t to the level σ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 55 publications
2
36
0
Order By: Relevance
“…According to the results of Calabrese et al (2017), future constraints from S4 experiment for a CMB signal with a tensorto-scalar ratio r ≃ 10 −3 will have a sensitivity level of σ r ≃ 5 × 10 −4 and the combination of PIXIE and S4 will enable a 5σ detection of r if larger than 2 × 10 −3 . Similar results where reported by Huang et al (2015) for different future planned CMB satellite experiments. Since, for V 2 (φ) inflation we find r ≃ 10 −3 , future experiments should allow us to differentiate it from normal inflation and possibly from the quadratic inflation V 1 (φ) which predict much smaller value of r. Moreover, Huang et al (2015) also showed that the CMB signal of tensor-to-scalar r ≃ 2 × 10 −3 will provide sensitivity level of σ nt ≃ 0.1 on tensor spectral tilt.…”
Section: Resultssupporting
confidence: 90%
“…According to the results of Calabrese et al (2017), future constraints from S4 experiment for a CMB signal with a tensorto-scalar ratio r ≃ 10 −3 will have a sensitivity level of σ r ≃ 5 × 10 −4 and the combination of PIXIE and S4 will enable a 5σ detection of r if larger than 2 × 10 −3 . Similar results where reported by Huang et al (2015) for different future planned CMB satellite experiments. Since, for V 2 (φ) inflation we find r ≃ 10 −3 , future experiments should allow us to differentiate it from normal inflation and possibly from the quadratic inflation V 1 (φ) which predict much smaller value of r. Moreover, Huang et al (2015) also showed that the CMB signal of tensor-to-scalar r ≃ 2 × 10 −3 will provide sensitivity level of σ nt ≃ 0.1 on tensor spectral tilt.…”
Section: Resultssupporting
confidence: 90%
“…Our results will have important implications following the detection of non-zero tensor-to-scalar ratio by a future CMB experiment (e.g., see Ref. [77] 3 and references therein). Such a detection, together with the data from PTAs and ground-based interferometers will put very tight limits on n t , with larger values of r being the most constraining.…”
Section: B Comparison With Theorymentioning
confidence: 78%
“…Therefore, using Eqs. (16) and (17) could not constrain the parameter β. Actually, the parameter β of the IR DBI model can be well constrained by the primordial non-Gaussianities.…”
Section: Models and Methodologymentioning
confidence: 99%